Successive xanthogranulomatous prostatitis after complete remission of metastatic prostate adenocarcinoma: An extremely rare case report with review of literatures - Che-Hsueh Yang (Urology Case Reports, 2020)
Xanthogranulomatous prostatitis is a rare occasion that mimics the prostate cancer in every aspect of clinical diagnosis. These two occasions require totally diverse therapeutics principles. Thus, emphasis should be exerted to distinguish them. The most precise tool to distinguish them is tissues’ evidence. However, another possible overlooking occasion is successive xanthogranulomatous prostatitis after complete remission under androgen deprivation therapy. This case demonstrated one metastatic prostate cancer with initial treatment of androgen deprivation therapy. PSA was suppressed to the lowest and then radical prostatectomy was performed. Hints from the specimen gave complete remission of cancer cell and development of xanthogranulomatous prostatitis.